Fundamental design paradigms for systems of three interacting magnetic nanodiscs - Derek Michael Forrester; Karl Kuerten; Feodor Kusmartsev (2011)
The magnetic properties of a system of three interacting magnetic elliptical disks are examined. For the various levels of uniaxial anisotropy investigated a complicated series of phase transitions exist. These are marked by the critical lines of stability that are demonstrated in an applied magnetic field plane diagram.